2006
DOI: 10.1093/molehr/gal044
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of the angiogenic regulators CYR61 (CCN1) and NOV (CCN3) in human placenta is associatedwith pre-eclampsia

Abstract: The pregnancy disorder pre-eclampsia (PE) is thought to be caused in part by shallow invasion of the extravillous trophoblast (EVT) leading to uteroplacental insufficiency and hypoxia. Here, we focused on the expressions of cysteine-rich 61 (CYR61, CCN1) and nephroblastoma overexpressed (NOV, CCN3), members of the CCN family of angiogenic regulators, in human placenta during normal pregnancy compared with pre-eclamptic and HELLP placentae using quantitative RT-PCR, western blotting and immunocytochemistry. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 48 publications
2
70
0
1
Order By: Relevance
“…35,36 The results of previous experiments using the choriocarcinoma cell line Jeg3 suggested that CCN3 causes an imbalance between the proliferation and migration of human trophoblast cells. 13,14,22 In the present study we found that both glycosylation forms of CCN1 and CCN3 proteins reduce the numbers of benign SGHPL-5 trophoblast cells, whereas in Jeg3 cells only CCN3 seems to regulate proliferation. Comparing the effect of CCNs on migration properties in both cell lines showed that Jeg3 trophoblast cells and SGHPL-5 cells are mostly stimulated by non-glycosylated CCN1 and CCN3.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…35,36 The results of previous experiments using the choriocarcinoma cell line Jeg3 suggested that CCN3 causes an imbalance between the proliferation and migration of human trophoblast cells. 13,14,22 In the present study we found that both glycosylation forms of CCN1 and CCN3 proteins reduce the numbers of benign SGHPL-5 trophoblast cells, whereas in Jeg3 cells only CCN3 seems to regulate proliferation. Comparing the effect of CCNs on migration properties in both cell lines showed that Jeg3 trophoblast cells and SGHPL-5 cells are mostly stimulated by non-glycosylated CCN1 and CCN3.…”
Section: Discussionsupporting
confidence: 57%
“…However, lower levels of CCN1 and CCN3 were detected in the sera of pregnant women with early-onset preeclampsia, a disease that is associated with insufficient trophoblast invasion. 22,23 These findings indicate that CCNs are involved in the regulation of cell biological events at the feto-maternal interface.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, EOPE exhibits placental histological changes related with reduced perfusion [10][11][12][13] as well as the anomalous structure of the peripheral villi and vasculature compared to respective controls identified by stereological analysis following EOPE, but not LOPE [13]. In addition, low placental levels of several pro-angiogenic factors have been reported in EOPE compared to LOPE or age-matched controls [14,15]. In particular, microarray analysis has described the lower expression of at least two angiogenesis-associated transcripts (Egfl7 and Acvrl1) in EOPE compared to LOPE or agematched controls [15].…”
Section: Introductionmentioning
confidence: 97%